SYNTHESIZE AND CHARACTERIZATION OF PVP/CA AND CHITOSAN NANOFIBER USING ELECTROSPINNING - MEURETTA ALAWIYAH PULUNGAN; RAFLI PANDU RAMADHANI; MEUTIA KAMILATUN NUHA AP IDJAN; IDA SRIYANTI; M RUDI SANJAYA; JAIDAN JAUHARI; RADIYATI UMI PARTAN (UNIVERISTAS PGRI MADIUN, 2023)
Nanofibers is one of the results of composites that have an important role in the industrial field, wound dressing, drug delivery and tissue engineering. Manufacturing of nanofibers can be carried out using electrospinning. Electrospinning is an easy, fast and simple technique for produced fibers with sizes ranging from micrometers to nanometers. We explained how to produce and the characteristics of nanofibers. The purpose of this study was to see the characterization of PVP/CA fiber. The fiber were made with consentration of PVP 10.4% (w/w) and mixed with variation of chitosan 0.5%;1%;1.5% (w/w). Process parameter that used in this research such us flowrate 0,20 ml/hour, high voltage 12 kV, and speed of drum is 200 rpm with the distances to needle tip of collector is 75 cm. The result showed that the morphology of fiber PVP/CA are bead fiber and bead free. The average diameter of PVP/CA fibers was 234;267;325 nm. Adding chitosan made the diameter of fibers increase. The XRD result shown that the fibers of PVP/CA/AE has an amorf phase. The fibers were potentially used in any sectors.